Research on wear characteristics of U-shaped elbows based on CFD-DEM coupling - Chang, Hao; Ji, Guangchao; Yu, Dehui; Peng, Guangjie; Hong, Shiming; Du, Jialin (Frontiers in Energy Research, 2023)
The C++ programming language is employed to improve the Computational Fluid Dynamics (CFD)- Discrete Element Method (DEM) coupling interface in this paper, the accuracy of solid-liquid two-phase flow numerical model are validated through experiments. Subsequently, the wear characteristics of the U-shaped elbows under different elbows spacing, bending diameter ratio, particle volume concentration, and particle size are investigated. The research results indicate that as the spacing between bends is increased, the phenomenon of particle sedimentation is intensified, and the maximum collision angle in elbow 2 is increased. The location of the maximum collision angle is closer to the outlet of elbow 2. However, both the collision frequency and wear rate are reduced due to the decrease in the number of particles. Smoother particle flow and a reduction in the collision angle and wear rate of particles on both bends are achieved by increasing the bend ratio. During the variation of the particle volume fraction from 0.5% to 7%, the increase in collision frequency and wear rate of both bends is slowed down. A greater decrease is observed in elbow 2, but the “shielding effect” is not observed. Furthermore, at low volume fractions, kinetic energy is lost by particles as they flow through elbow 1, resulting in a lower average wear rate in elbow 2 compared to elbow 1. Conversely, at high volume fractions, the opposite effect occurs. Finally, when keeping the particle volume fraction constant, an increase in the particle size leads to a smaller wear area in both bends. The wear rate in elbow 1 increases at a slower rate, while the wear rate in elbow 2 exhibits an initial increase followed by a decrease trend.